The Grade of Dengue Hemorrhagic Fever in Children - Suradi Efendi; Nour Sriyanah; Hendrika Risa Buntu; Ilham Syam; Suarni Suarni; Djunaedi Djunaedi (GLOBAL HEALTH SCIENCE GROUP, 2022)
Dengue hemorrhagic fever is caused by the dengue virus, which infects humans through mosquito-mediated, and is characterized by severe clinical symptoms such as fever, hemorrhage, hematoma, and signs of circulatory collapse before the shock occurs. The more critical the condition of a child with suspected dengue fever when admitted to the hospital, the higher the degree of illness. According to the Ministry of Health, in 2015, there were 129,650 cases of the disease, and 1,071 people died (0.83%). This research aims to describe the incidence of dengue hemorrhagic fever in children in Seruni treatment room, dr La Palaloi regional hospital, Maros Regency. The type of research is descriptive, using a quantitative approach, with a total population of 92 people. Sampling used a total sampling technique with an observation sheet instrument to take secondary data in the medical record room. The results showed that from 92 samples of children with Dengue Hemorrhagic Fever (DHF), there were 49 people (53.3%) suffering from DHF grade II, 60 people (65.2%) had a fever for more than seven days, most of whom had DHF grade II as many as 34 people (37.0). %), and 50 people (54.3%) had poor nutritional status, most of whom suffered from DHF grade II, and as many as 30 people (32.6%). This research concludes that the duration of fever and the nutritional status of children determine the degree of dengue fever. Further researchers are encouraged to use more diverse sample and use other research designs to refine the factors that influence DHF in children.